Carried Along. (February 2023) - Ely, Eugene Wesley
As a physician, the hardest days in medicine are when I endure great distance from the Lord in my bedside interactions with patients and families. They make me feel like driftwood without vocational direction. Given the enormity of what critically ill patients are experiencing, emotional detachment from Jesus and those I am serving creates swells of grief for me as a Catholic physician. In the intensive care unit, I tend to gravitate to big and bold occurrences. Unfortunately, one tendency I have is to think that small events yield small outcomes, while big events yield big outcomes. Such is not the case with God, whom I tend to force into finite scales when, in truth, the Creator of the universe has no limits. This essay highlights an experience in which God brought a deeper understanding of His grace from a seemingly monotonous patient encounter. I am reminded that because of God's presence in my relationship with each person, "Nothing shall be impossible." (Lk 1:37).